Принцип антропології права у теоретико-правових дослідженнях сучасності - Завальнюк, Володимир Васильович; Завальнюк, Владимир Васильевич; Zaval'njuk, Vladimir (My University, 2012)
The article studies the anthropological trends approval priority of the individual and subjective rights in modern legal thought and found that in many countries, legal concepts, based on the anthropological principle of law, enshrined the principles of decent human life, freedom, equality. Revealed that the anthropological principle evident in these theoretical and legal fields as neo, revived the theory of natural law, Kantianism, intersubektivnoe direction phenomenological-hermeneutical philosophy of law.
Завальнюк В. В. Принцип антропології права у теоретико-правових дослідженнях сучасності / В. В. Завальнюк // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 19-29.
Keywords: принцип антропології права; особистість; неопозитивізм; теорії відродженого природного права; неокантіанство; інтерсуб'єктивний напрямок; феноменолого-герменевтична філософія права; принцип антропологии права; неокантианство; интерсубъективное направление; феноменолого-герменевтическая философия права; Principle of anthropology of law; individual; neopositivism; revived the theory of natural law; Kantianism; intersubektivny direction; phenomenological-hermeneutical philosophy of law